Method for preparing nano-twinned copper layer by high-frequency pulsed electric spark wire cutting

The process parameters are adjusted by high-frequency pulsed electric spark wire cutting method, and the production efficiency of nanotwin copper layers in the prior art is solved, and rapid and efficient preparation of nanotwin copper layers is achieved.

CN115430874BActive Publication Date: 2025-03-28WUHAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211004640.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-22
Publication Date
2025-03-28
Estimated Expiration
2042-08-22

AI Technical Summary

Technical Problem

The methods for preparing nanotwin copper layers in the prior art have problems such as cumbersome maintenance of equipment and plating solutions and low production efficiency.

Method used

The nanotwin copper layer is prepared by high-frequency pulsed electric spark line cutting method. By adjusting parameters such as pulse width, pulse interval and power amplifier tube number, a fast and adjustable preparation speed and efficient production process are achieved.

Benefits of technology

The rapid preparation of nanotwin copper layer was achieved, the production efficiency was significantly improved, the preparation time was shortened to 3 to 20 minutes, and the structure of the prepared nanotwin copper layer was not significantly different from the electrodeposition technology products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115430874B_ABST
    Figure CN115430874B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a nano-twinned copper layer by high-frequency pulsed electric spark wire cutting, the method comprising: cutting the surface of a copper alloy material by high-frequency pulsed electric spark wire cutting to form a nano-twinned copper layer on the surface of the copper alloy material; the process parameters of the high-frequency pulsed electric spark wire cutting include: pulse width 35-80μs, pulse interval 8-11μs, and power amplifier tube number 4-6A. The method for preparing a nano-twinned copper layer by high-frequency pulsed electric spark wire cutting provided by the present invention has a thickness of 10-25μm, a thickness of the nano-twinned copper twins is less than 100nm, and there is no significant difference in structure with the nano-twinned copper prepared by electrodeposition technology. Compared with the conventional method for preparing a nano-twinned copper layer by electrodeposition, the present invention is simple and convenient to operate, has a higher preparation speed, significantly improves production efficiency, and can further adjust the preparation speed by adjusting parameters such as pulse width, pulse interval, and power amplifier tube number.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material processing, and in particular relates to a method for preparing a nano twinned copper layer by adopting high-frequency pulse electric spark wire cutting. Background Art

[0002] Copper is widely used in power electronics, energy and petrochemicals, mechanical metallurgy, transportation, light industry and emerging industries due to its excellent electrical and thermal conductivity and good ductility. It is an important raw material for the production of components such as conductors and printed circuit boards with integrated circuits. With the improvement of precision manufacturing requirements, the role of copper metal materials in modern science has become more important. At the same time, the performance requirements for copper materials are also constantly increasing. Nanotwinned metal materials have excellent mechanical properties, including high strength and good plasticity. The high-density twin boundaries in them can effectively hinder dislocation movement. In addition to excellent mechanical properties, nanotwinned copper has also attracted the attention of researchers due to its high electrical conductivity and thermal stability. As the research on nanotwins becomes more mature, people realize that the ordered nanotwin boundaries are the perfect interface for reinforcing materials. If nanotwinned copper layers can be prepared on a large scale, it will inevitably bring great economic output value.

[0003] At present, the method for preparing nano-twinned copper layers is mainly based on electrodeposition technology, which can be specifically divided into direct current electrodeposition and pulse electrodeposition technology. However, the existing technology still has problems such as cumbersome maintenance of electrodeposition solution, slow deposition speed, and low production efficiency.

[0004] Based on this, providing a new method for producing nano-twinned copper layers to solve the problems of cumbersome equipment and plating solution maintenance, low production efficiency, etc. in the prior art is a technical problem that needs to be solved urgently. Summary of the invention

[0005] The purpose of the present invention is to address the deficiencies of the prior art and provide a method for preparing a nano-twinned copper layer with fast and adjustable preparation speed and high production efficiency.

[0006] In order to solve the above technical problems, the present invention adopts the following technical scheme: a method for preparing a nano-twin copper layer by high-frequency pulse electric spark wire cutting is provided, the method comprising: cutting the surface of a copper alloy material by high-frequency pulse electric spark wire cutting to form a nano-twin copper layer on the surface of the copper alloy material; the process parameters of the high-frequency pulse electric spark wire cutting include: pulse width 35 to 80 μs, pulse interval 8 to 11 μs, and power amplifier tube number 4 to 6A.

[0007] High-frequency pulsed wire-cutting machining, also known as wire cutting, uses a continuous thin metal wire that moves along its axis as a tool electrode. Based on the electro-corrosion effect of pulsed discharge between the electrode wire and the workpiece, it removes excess metal to meet the processing requirements of the workpiece. During processing, the workpiece is connected to the positive electrode of the pulse power supply, and the electrode wire is connected to the negative electrode. Under the action of the electric field, electrons collide with the positive electrode at high speed, and positive ions collide with the negative electrode at high speed, forming an ionized conductive channel. Countless collisions occur between ions, forming instantaneous local high temperature in the discharge channel, melting or vaporizing the local workpiece. The nozzle sprays a cutting fluid with insulating properties into the processing area at a certain pressure to take away the etched material. The cutting trajectory of the metal wire is controlled by CNC programming to achieve the cutting of metal samples.

[0008] Based on an accidental discovery in an experiment, the present invention proposes a method for preparing a nano-twin copper layer on the surface of a copper alloy using electric sparks from wire cutting. The method sets the relevant parameters of wire cutting and uses the process of automatic wire cutting by a machine to generate electric sparks during the cutting process, thereby achieving the preparation of a nano-twin copper layer on the surface of a copper alloy. Compared with the method of preparing nano-twin copper by electroplating, the preparation method provided by the present invention is simple to operate, the process is easy to control, and the preparation time is short. The preparation of the nano-twin copper layer can be completed in only 3 to 20 minutes.

[0009] Furthermore, the copper alloy material is preferably a bronze alloy.

[0010] In some preferred embodiments, the copper alloy material is a nickel-aluminum bronze alloy. The main components of the nickel-aluminum bronze alloy include, by weight percentage: Cu 77-82wt%, Al 7.0-11.0wt%, Ni 3.0-6.0wt%, Mn 0.5-4.0wt%, and Fe 2.0-6.0wt%.

[0011] Furthermore, in the present invention, the state of the nickel-aluminum bronze alloy can be an extruded state, a cast state, a solid solution state or other states, all of which can produce the desired nano-twinned copper layer.

[0012] Furthermore, the thickness of the copper alloy material is 1 to 800 mm. Preferably, the thickness of the copper alloy material is 3 to 50 mm, and the parameters of the wire cutting are: pulse width 40 μs, pulse interval 11 μs, and power amplifier tube number 6A.

[0013] Furthermore, in the cutting fluid of the high-frequency pulse electric spark wire cutting, the volume ratio of the wire cutting emulsion to water is 1:10-12.

[0014] Furthermore, the cutting wire of the high-frequency pulse electric spark wire cutting is selected from one of molybdenum wire, copper wire or tungsten-molybdenum-copper alloy wire.

[0015] Furthermore, the high-frequency pulse voltage of the high-frequency pulse electric spark wire cutting is 220V.

[0016] In some preferred embodiments, the method for preparing a nano-twinned copper layer by high-frequency pulsed electric spark wire cutting comprises the following steps:

[0017] S1. After grinding and cleaning, the copper alloy material is clamped on a fixture, and the fixture is fixed on a wire cutting workbench;

[0018] S2, turn on the pulse power supply and make the cutting fluid circulate;

[0019] S3. According to the thickness of the copper alloy material, the process parameters of the high-frequency pulsed electric spark wire cutting are set so that the cutting wire contacts the surface of the copper alloy material, spark discharge is formed under the action of the high-frequency pulse voltage, and a nano-twinned copper layer is formed on the surface of the copper alloy material.

[0020] During the above operation, when the cutting wire contacts the copper alloy, spark discharge is formed under the action of high-frequency pulse voltage, and a large amount of heat is instantly generated in the spark channel, causing the copper alloy to melt and corrode, and impurities to flow down along with the liquid; at the same time, a nano-twin copper layer of a certain thickness is formed on the cutting surface of the copper alloy.

[0021] Furthermore, in step S3, the process parameters of high-frequency pulsed electric spark wire cutting are set according to the thickness of the copper alloy material:

[0022] When the thickness of the copper alloy material is 1-60 mm, the parameters of the wire cutting are: pulse width 35-50 μs, pulse interval 9 μs, power amplifier tube number 4A; when the thickness of the copper alloy material is 60-100 mm, the parameters of the wire cutting are: pulse width 43-58 μs, pulse interval 8 μs, power amplifier tube number 4A; when the thickness of the copper alloy material is 100-150 mm, the parameters of the wire cutting are: pulse width 50-58 μs, pulse interval 9 μs, power amplifier tube number 4A The number of power amplifier tubes is 5A; when the thickness of the copper alloy material is 300mm, the parameters of wire cutting are: pulse width 65-70μs, pulse interval 10μs, and the number of power amplifier tubes is 5A; when the thickness of the copper alloy material is 600mm, the parameters of wire cutting are: pulse width 70μs, pulse interval 10μs, and the number of power amplifier tubes is 5A; when the thickness of the copper alloy material is 800mm, the parameters of wire cutting are: pulse width 80μs, pulse interval 11μs, and the number of power amplifier tubes is 6A.

[0023] Furthermore, the thickness of the nano-twinned copper layer obtained by the present invention is 10 to 25 μm, and the thickness of the copper twins of the nano-twinned copper layer is less than 100 nm. It usually takes several hours to prepare the nano-twinned copper layer of the same thickness using conventional electrodeposition technology, while the preparation time required by the present invention is only 3 to 20 minutes, and the nano-copper twins obtained by the present invention have no obvious difference from the products of the electrodeposition technology in terms of microstructure. In comparison, the present invention has significant advantages in improving preparation efficiency and shortening preparation time.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) The method for preparing the nano-twinned copper layer provided by the present invention adopts high-frequency pulsed electric spark wire cutting to prepare the nano-twinned copper layer. The preparation speed is adjusted by adjusting the parameters such as pulse width, pulse interval, and number of power amplifier tubes during the high-frequency pulsed electric spark wire cutting process. Generally, the cutting of a 5mm×10mm copper alloy surface can be completed in 3 minutes, and a nano-twinned copper layer with a thickness of 10 to 25μm is prepared on the surface.

[0026] (2) Compared with the method for preparing nano-twinned copper layer by electrodeposition in the prior art, the method for preparing nano-twinned copper layer by high-frequency pulsed electric spark wire cutting provided by the present invention is simple and convenient to operate, has a faster production speed, and significantly improves production efficiency. The thickness of the prepared nano-twinned copper twins is less than 100 nm, and there is no obvious difference in structure between the nano-twinned copper and the nano-twinned copper prepared by electrodeposition technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The nano twin layer structure of the extruded nickel aluminum bronze alloy sample in Example 1 of the present invention, wherein (a) is a low-magnification wide-field SEM image of the spark-affected zone; (b) is a high-magnification SEM image of the nano twins;

[0028] Figure 2 The nano twin layer structure of the extruded nickel aluminum bronze alloy sample in Example 2 of the present invention, wherein (a) is a low-magnification wide-field SEM image of the spark-affected zone; (b) is a high-magnification SEM image of the nano twins;

[0029] Figure 3 The nano twin layer structure of the extruded nickel aluminum bronze alloy sample in Example 3 of the present invention, wherein (a) is a low-magnification wide-field SEM image of the spark-affected zone; (b) is a high-magnification SEM image of the nano twins;

[0030] Figure 4 The nano twin layer structure of the extruded nickel aluminum bronze alloy sample in Example 4 of the present invention, wherein (a) is a low-magnification wide-field SEM image of the spark-affected zone; (b) is a high-magnification SEM image of the nano twins;

[0031] Figure 5 The nano twin layer structure of the cast nickel aluminum bronze alloy sample in Example 5 of the present invention, wherein (a) is a low-magnification wide-field SEM image of the spark-affected zone; (b) is a high-magnification SEM image of the nano twins;

[0032] Figure 6 This is the nanotwin layer structure of the solid solution nickel-aluminum bronze alloy sample in Example 6 of the present invention, (a) high-magnification SEM image of the nanotwin. DETAILED DESCRIPTION

[0033] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0035] The present invention is further described below in conjunction with specific examples. Examples 1-4 of the present invention all take nickel-aluminum bronze alloy as an example to prepare the nano twin layer, but this is not intended to be a limitation of the present invention.

[0036] Embodiment 1:

[0037] The steps of preparing a nano-twinned copper layer on the surface of a nickel-aluminum bronze alloy are as follows:

[0038] After grinding and cleaning the extruded nickel-aluminum bronze alloy, clamp it on the fixture, and fix the fixture on the wire cutting workbench. (The alloy thickness is 5mm, and the section size is 5mm×10mm) Turn on the high-frequency pulse power supply and circulate the cutting fluid. Set the wire cutting parameters as follows: pulse width 40μs, pulse interval 8μs, power amplifier tube number 4A. When the cutting wire contacts the copper alloy, spark discharge is formed under the action of the high-frequency pulse voltage, and a large amount of heat is instantly generated in the spark channel, causing the copper alloy to melt and corrode. At the same time, a nano-twin copper layer of a certain thickness is formed on the cut surface of the copper alloy. The above cutting process is completed within 3 minutes.

[0039] After high-frequency pulsed electric spark wire cutting, the nano twin layer structure of the nickel aluminum bronze alloy sample in Example 1 is as follows Figure 1 Among them, (a) is a low-magnification wide-field SEM image of the spark-affected zone, showing that the thickness of the nano-twin region is about 25 μm; (b) is a high-magnification SEM image of the nano-twin, showing that the thickness of the twin is less than 100 nm.

[0040] Embodiment 2:

[0041] Except for setting the wire cutting parameters as: pulse width 40 μs, pulse interval 8 μs, and number of power amplifier tubes 5A, the process flow and other process parameters of this embodiment are the same as those of Embodiment 1.

[0042] Figure 2 The nanotwin layer structure of the nickel-aluminum bronze alloy sample in Example 2. (a) is a low-magnification wide-field SEM image of the spark-affected zone, showing that the thickness of the nanotwin region is about 20 μm; (b) is a high-magnification SEM image of the nanotwin, showing that the twin thickness is less than 100 nm.

[0043] Embodiment 3:

[0044] Except for setting the wire cutting parameters as: pulse width 40 μs, pulse interval 9 μs, and number of power amplifier tubes 4A, the process flow and other process parameters of this embodiment are the same as those of embodiment 1.

[0045] Figure 3 The nanotwin layer structure of the nickel-aluminum bronze alloy sample in Example 3. (a) is a low-magnification wide-field SEM image of the spark-affected zone, showing that the thickness of the nanotwin region is about 13 μm; (b) is a high-magnification SEM image of the nanotwin, showing that the twin thickness is less than 100 nm.

[0046] Embodiment 4:

[0047] Except for setting the wire cutting parameters as: pulse width 40 μs, pulse interval 9 μs, and number of power amplifier tubes 5A, the process flow and other process parameters of this embodiment are the same as those of Embodiment 1.

[0048] Figure 4 The nano twin layer structure of the nickel aluminum bronze alloy sample in Example 4. (a) is a low-magnification wide-field SEM image of the spark affected area, showing that the thickness of the nano twin area is about 10 μm; (b) is a high-magnification SEM image of the nano twin, showing that the twin thickness is less than 100 nm.

[0049] Embodiment 5:

[0050] After the cast nickel-aluminum bronze alloy is polished and cleaned, it is clamped on a fixture, and the fixture is fixed on a wire cutting workbench (the alloy thickness is 5 mm, and the section size is 5 mm×10 mm). The wire cutting parameters are set as follows: pulse width 50 μs, pulse interval 8 μs, and power amplifier tube number 4A. The process flow and other process parameters of this embodiment are the same as those of embodiment 1.

[0051] Figure 5 The nano twin layer structure of the nickel aluminum bronze alloy sample in Example 5. (a) is a low-magnification wide-field SEM image of the spark affected area, showing that the thickness of the nano twin area is about 12 μm; (b) is a high-magnification SEM image of the nano twin, showing that the twin thickness is less than 100 nm.

[0052] Embodiment 6:

[0053] After grinding and cleaning the solid solution nickel aluminum bronze alloy, clamp it on the fixture, and fix the fixture on the wire cutting workbench (the alloy thickness is 5mm, and the section size is 5mm×10mm). Set the wire cutting parameters as follows: pulse width 50μs, pulse interval 8μs, power amplifier tube number 4A. The process flow and other process parameters of this embodiment are the same as those of embodiment 1.

[0054] Figure 6 The nano twin layer structure of the nickel aluminum bronze alloy sample in Example 6. (a) is a high-magnification SEM image of the nano twins, showing that the twin thickness is less than 100 nm.

[0055] The above are only preferred embodiments of the present invention, and are not intended to limit the implementation methods and protection scope of the present invention. Those skilled in the art should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the contents of the specification of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a nano-twinned copper layer by high-frequency pulsed electric spark wire cutting, characterized in that: The surface of the copper alloy material is cut by high-frequency pulsed electric spark wire cutting to form a nano-twinned copper layer on the surface of the copper alloy material; the thickness of the nano-twinned copper layer is 10-25 μm; The thickness of the copper twins of the nano-twinned copper layer is less than 100 nm; The process parameters of the high-frequency pulse electric spark wire cutting include: pulse width 35~80μs, pulse interval 8~11μs, and power amplifier tube number 4~6A.

2. The method according to claim 1, characterized in that The copper alloy material is nickel-aluminum bronze alloy.

3. The method according to claim 2, characterized in that The state of the nickel-aluminum bronze alloy is selected from one of an extruded state, a cast state or a solid solution state.

4. The method according to claim 3, characterized in that The thickness of the nickel-aluminum bronze alloy is 3-50 mm.

5. The method according to claim 1, characterized in that In the cutting fluid of the high-frequency pulse electric spark wire cutting, the volume ratio of the wire cutting emulsion to water is 1:10-12.

6. The method according to claim 1, characterized in that The cutting wire of the high-frequency pulse electric spark wire cutting is selected from one of molybdenum wire, copper wire or tungsten-molybdenum-copper alloy wire.

7. The method according to claim 1, characterized in that The high-frequency pulse voltage of the high-frequency pulse electric spark wire cutting is 220V.

8. The method according to any one of claims 1 to 7, characterized in that The method comprises the following steps: S1. After grinding and cleaning, the copper alloy material is clamped on a fixture, and the fixture is fixed on a wire cutting workbench; S2, turn on the pulse power supply and make the cutting fluid circulate; S3. According to the thickness of the copper alloy material, the process parameters of the high-frequency pulsed electric spark wire cutting are set so that the cutting wire contacts the surface of the copper alloy material, spark discharge is formed under the action of the high-frequency pulse voltage, and a nano-twinned copper layer is formed on the surface of the copper alloy material.

Citation Information

Patent Citations

  • One-step preparation method of metal material surface with super-hydrophobic micro-nano structure

    CN103317198A

  • Method for preparing nano twin crystal layer on surface of metal titanium

    CN106756691A